Peran BMT Dalam Peberdayaan Usaha Mikro Terhadap Persepsi Nasabah : (Studi Kasus BMT Capem Gending Probolinggo) - Yeni Kartikawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Financial institutions have played a very large role in the development and growth of modern industrial society. BMT is included in the Sharia Financial Institutions which are operated on the principle of profit sharing, trying to grow and develop micro, small and medium enterprises, in order to raise the level and dignity and defend the interests of the poor. The aim of this research is to determine the role of BMT in empowering micro businesses and the potential of businesses financed at Baitul mal wa tamwil (BMT) to develop economic activities so that they provide positive, prosperous and of course more independent results. This research is qualitative research with a descriptive research type, and the research data is taken from first-hand data, namely customer perceptions and second-hand statements that can be trusted. Data collection techniques include interviews, observations and information from books, articles, journals and theses. Research findings show that BMT plays an important role in empowering micro businesses by providing financing in accordance with sharia and cooperative work operational agreements. That way, MSMEs will become more advanced and able to absorb workers, which of course will help a lot in economic development and alleviating poverty due to reduced employment opportunities.